1989
DOI: 10.2960/j.v9.a11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Growth of Northern Shrimp (Pandalus borealis) from Four Regions of the Northwest Atlantic

Abstract: Modal analyses of carapace length frequencies and interpretation of biological data for the northern shrimp (Panda/us borealis) indicate variation in both age at sex change and growth rate for some Northwest Atlantic populations. The first female age (the species is protendrous) varied from 6 in the southernmost area to 7 and possibly 8 in more northerly areas. The observed differences could not be related to differences in environmental temperature. Overlapping of modes in the length frequency data was severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The most discussed factor in the literature is ambient temperature which is considered to explain differences in age at first spawning (Apollonio et al 1986) and CPL at age (Shumway et al 1985). My results from the temporally isolated shrimp populations in Gullmarsfjorden growing at different mean ambient temperatures during different deep water stagnation periods indicate that there is no correlation between temperature and growth rate within the temperature interval of 4 to 6 "C. A similar observation was made by Parsons et al (1989) comparing Northern shrimp growth in the temperature interval of 2 to 4 "C from 4 regions of the Northwest Atlantic.…”
Section: Differences In Male and Female Growthmentioning
confidence: 56%
“…The most discussed factor in the literature is ambient temperature which is considered to explain differences in age at first spawning (Apollonio et al 1986) and CPL at age (Shumway et al 1985). My results from the temporally isolated shrimp populations in Gullmarsfjorden growing at different mean ambient temperatures during different deep water stagnation periods indicate that there is no correlation between temperature and growth rate within the temperature interval of 4 to 6 "C. A similar observation was made by Parsons et al (1989) comparing Northern shrimp growth in the temperature interval of 2 to 4 "C from 4 regions of the Northwest Atlantic.…”
Section: Differences In Male and Female Growthmentioning
confidence: 56%
“…For example, Butler (1964) and Charnov (1979) suggested that populations at lower latitudes have a higher proportion of EMFs because those individuals grow more rapidly (Rasmussen 1953). There are few conclusive reports showing which factors govern growth in pandalid shrimps, and the effect of water-temperature fluctuations in any one area is not clear (Shumway et al 1985, Apollonio et al 1986, Parsons et al 1989, Bergström 1992. In shallow water, water temperature and/or the availability of food is much more variable among localities than in the deep sea.…”
Section: Discussionmentioning
confidence: 99%
“…, 1985; Nilssen and Hopkins, 1991). Parsons et al. (1989) inferred an increase in longevity from 6 to 8 yr from the southern Newfoundland–Labrador Shelf to Davis Strait.…”
Section: Introductionmentioning
confidence: 99%